Risk Stratification of Acute Invasive Fungal Rhinosinusitis in Patients With Hematologic Pathology. (18th June 2022) - Navuluri, Sriram; Gardner, James Reed; Vickers, Donald; Mohler, Samantha; King, Deanne; Kanaan, Alissa
Abstract : Objective: The purpose of this study is to identify objective perioperative diagnostic factors for acute invasive fungal rhinosinusitis (AIFS) to create a diagnostic scoring system using objective criteria. Methods: Retrospective case–control study performed at an academic, tertiary care center. Biopsy‐proven cases of AIFS identified from pathology records (2015–2019) were compared to patients the otolaryngology service was consulted to "Rule out AIFS" in the year 2019, only including those with underlying hematologic malignancy. Eighteen patients with AIFS and 20 patients without were included. One and two tailed T‐tests were used for p‐values. Receiver operating characteristic curves were generated for the significant data, and Youden's J‐statistic was used to create the ideal cutoff values for each. Likelihood ratios were used to give a power for the scoring system. Results: Compared to patients with non‐hematologic malignancy‐related AIFS, patients with hematologic malignancy‐related AIFS have significantly elevated C‐reactive protein (CRP) and blood glucose; while albumin, hematocrit, platelet count, and absolute neutrophil count (ANC) were found to be significantly lower. In addition, Lund‐Mackay score asymmetry, extra‐sinus spread, aspergillus antigen, and pre‐existing diabetes mellitus correlated with disease. A scoring system with three categories: AIFS Unlikely, Indeterminate/AIFS Suspicious, and AIFS Highly Likely was developed. Conclusion: Patients with hematologic malignancy‐related AIFS have measurable differences in lab values and standard imaging that could be used in determining the diagnostic probability of AIFS including: CRP, albumin, hematocrit, platelets, ANC, blood glucose, aspergillus antigen, Lund‐Mackay score asymmetry, extra‐sinus spread, and pre‐existing diabetes mellitus. A novel scoring system was proposed that will require prospective validation. Level of Evidence: 3 Laryngoscope, 133:1059–1064, 2023 Abstract : This study sought to identify objective perioperative diagnostic factors for acute invasive fungal rhinosinusitis (AIFS) to develop a diagnostic scoring system. A retrospective case‐control study was developed identifying patients with underlying hematologic malignancy with concerns for AIFS. Patients with hematologic malignancy‐related AIFS have measurable differences in lab values and standard imaging, which were utilized to develop a novel scoring system.